2017
DOI: 10.7717/peerj.3531
|View full text |Cite
|
Sign up to set email alerts
|

Extensive analysis of native and non-native Centaurea solstitialis L. populations across the world shows no traces of polyploidization

Abstract: Centaurea solstitialis L. (yellow starthistle, Asteraceae) is a Eurasian native plant introduced as an exotic into North and South America, and Australia, where it is regarded as a noxious invasive. Changes in ploidy level have been found to be responsible for numerous plant biological invasions, as they are involved in trait shifts critical to invasive success, like increased growth rate and biomass, longer life-span, or polycarpy. C. solstitialis had been reported to be diploid (2n = 2x = 16 chromosomes), ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
3
18
2
Order By: Relevance
“…Lysak et al 2000;Savas et al 2019). As our Californian samples varied 1.21fold, YST demonstrated moderate variation on par with a previous survey in the system (Irimia et al 2017) and with observations in several other systems including Dactylis glomerata (Creber et al 1994), Arachis duranensis (Temsch and Greilhuber 2001), Lagenaria siceraria (Achigan-Dako et al 2008) and Phragmites australis (Pysek et al 2018). The variation we observed in YST is also similar to systems that have demonstrated significant associations between genome size and important plant traits (Pysek et al 2018), or with environmental variables (Benor et al 2007;Achigan-Dako et al 2008;Bilinski et al 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lysak et al 2000;Savas et al 2019). As our Californian samples varied 1.21fold, YST demonstrated moderate variation on par with a previous survey in the system (Irimia et al 2017) and with observations in several other systems including Dactylis glomerata (Creber et al 1994), Arachis duranensis (Temsch and Greilhuber 2001), Lagenaria siceraria (Achigan-Dako et al 2008) and Phragmites australis (Pysek et al 2018). The variation we observed in YST is also similar to systems that have demonstrated significant associations between genome size and important plant traits (Pysek et al 2018), or with environmental variables (Benor et al 2007;Achigan-Dako et al 2008;Bilinski et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Here, we investigate evolutionary causes of genome size variation in the invasive species yellow starthistle, Centaurea solstitialis L., in the Asteraceae (hereafter, YST). YST is an annual, obligately outcrossing, diploid thistle (2n=16, Heiser and Whitaker 1948;Widmer et al 2007;Öztürk et al 2009), and previous work has suggested that genome size is variable within its invaded ranges (Irimia et al 2017). YST is invasive in the United States, where it is particularly problematic in California and now occupies over 12 million acres of land (Maddox and Mayfield 1985;Pitcairn et al 2006).…”
mentioning
confidence: 99%
“…Yellow starthistle (Centaurea solstitialis L., Asteraceae) is an obligately outcrossing annual plant, diploid throughout its range (102). Plants form a taproot and grow as a rosette through mild winter and/or spring conditions, bolting and producing flowering heads (capitula) throughout the summer.…”
Section: Methodsmentioning
confidence: 99%
“…Centaurea solstitialis (Asteraceae) is a globally distributed herbaceous annual plant species, diploid throughout its range (Irimia et al., 2017), and associated with human disturbance. The species has a branched appearance with reproductive structures found at the end of each branch.…”
Section: Methodsmentioning
confidence: 99%